PILIHAN RASIONAL PEMERINTAH SUDAN MENERIMA PROSES REFERENDUM DI SUDAN SELATAN - Atina Rosydiana (2014)
The Process of South Sudan‟s Referendum was finally agreed by Sudan Government Post Naivasha‟s Agreement 2005 as the part of Comprehensive Peace Agreement. This policy was agreed based on several reasons considered to The Rational Theory which uphold the result utilization. Referendum happened based on three basic mechanisms. First, as the bargaining of elite level, such executive and legislature in behalf of power. Second, in the sake of legitimacy and public trust and or to change the status quo. Third, to defend regime and executive may take better position. The result consist of domestic politic stability, economic and military sector, and international context as the consideration. The acceptance of referendum process brought more good than harm even it still left some weakness indeed. Referendum yelled as the conflict resolution of Sudan – South Sudan‟s long dispute. Keywords: Referendum, Sudan, South Sudan